Procedures for the evaluation of sweetpotato trials - Grüneberg, W.J.; Eyzaguirre, R.; Díaz, F.; Boeck, B. de; Espinoza, J.; Swanckaert, J.; Dapaah, H.; Andrade, M.I.; Makunde, G.S.; Agili, S.; Ndingo‐Chipungu, F.P.; Attaluri, S.; et al. (International Potato Center, 2019)
Breeding programs involve large investments of time and money, but can pay very large returns on investment in the form of improved varieties that benefit farmers, societies and the environment. International breeding efforts involving multiple partners and targeting regionally important constraints have great potential for efficiently and rapidly achieving impact. Standardised information on the performance of progenies and selected clones across environments assists breeders to efficiently make decisions about selection and variety releases. Standardised methods also facilitate the reporting of breeding program results to the agencies that support us. This manual of procedures for the evaluation and analysis of sweetpotato trials provides standard methods for partners in CIP’s global breeding efforts.